Purpose of education and spiritual potential ; What is your definition - Indrawati, Turmudi; Rohana, Hamzah; Sarimah, Ismail; Muhammad Afzamiman, Aripin; Nor Hasrina, Mohamad; Haslinda, Hashim; Nur Qistina, Andin (Penerbit UTM Press, 2017)
Developing and producing a holistic human capital has been a major concern to Malaysian education system. Therefore, the National Education Philosophy has been formed based on a mission to produce a balance and holistic individual in terms of physical, emotional, spiritual and intellectual based on firm belief and devotion to God. In contrary, education system nowadays is more focused on intellectual and practical aspects, whereas spiritual dimension has being neglected. Spiritual dimension is taught separately in spiritual subjects and the responsibility to teach is given to the educators in the areas concerned. Needs analysis conducted on technical and engineering educators from three engineering faculty at UTM shows that majority of participants do not really understand the real purpose of education, the meaning of spiritual potential and also how spiritual potential can be developed through Technical and Engineering Education. Therefore, there is a possibility that this potential has been less developed through Engineering Education courses in UTM.